Phytochemical Analysis, Antioxidant, and Antibacterial Properties of Waste Fruit Peels (Orange, Banana, Apple, and Lemon) - Anjali Kumari Sah; Kripa Pandey; Aaraju Khadka; Surjina Shrestha; Sagar Kandel; Sudip Bhandari; Era Tuladhar (Nepal Journal of Biotechnology)
Fruit peels contain secondary metabolite compounds with potential antioxidant properties. This research aims to investigate the phytochemical composition and antioxidant properties of extracts from the peels of orange, banana, apple, and lemon. The peels were extracted using distilled water through cold percolation. The percentage yield was determined, followed by qualitative phytochemical screening. Total phenolic and flavonoid presence were quantified. Additionally, antioxidant properties were evaluated using the DPPH radical scavenging assay, and antibacterial activities were assessed. The yield percentage of fruit peel extracts followed the order: of banana > apple > orange > lemon. The phytochemical analysis illustrated the presence of the alkaloid, reducing and non-reducing sugars, coumarins, saponins, flavonoids, phenols, tannins, glycosides, terpenoids, and steroids. TPC values (mg GAE/g) were highest in lemon (132.22 ± 3.95) and lowest in banana (60.69 ± 2.005). TFC values (mg QE/g) were highest in orange (4.373 ± 1.667) and lowest in lemon (1.204 ± 0.277). Antioxidant activity (DPPH scavenging) was highest in oranges (56.29%) and lowest in bananas (17.11%). The antibacterial activity of fruit peel, tested using agar well diffusion, showed no inhibition against E. coli, K. pneumoniae, P. aeruginosa, and S. aureus. The research quantified TPC and TFC and evaluated antioxidant and antibacterial activities. While the extracts demonstrated moderate antioxidant potential, their antibacterial properties were negative, suggesting they may be more suitable as natural antioxidants rather than antimicrobial agents.